Zika Virus Congenital Syndrome and MTOR gene variants: insights from a family of dizygotic twins. Issue 4 (April 2021) - de O. da Silva, Luciana Reboredo; Oliveira, Pablo; Sardi, Silvia; Soares, Gubio; Bandeira, Antônio Carlos; Costa, Ryan dos Santos; Rafaels, Nicholas; Campbell, Monica; Brunetti, Tonya; Crooks, Kristy; Daya, Michelle; Teixeira, Maria Glória; et al.
Abstract: Congenital Zika virus syndrome (CZS) is associated with damage to neural progenitor cells by ZIKA virus infection. There are no accurate statistics on the percentage of pregnant mothers who have had babies affected by the syndrome. Few cases of discordant twins have been described in the literature and, therefore, we hypothesize that the genetic background of the progeny and/or mother may play a role in the fate of the syndrome. We performed a complete exome sequencing in a set of dizygotic individuals and their parents. After that, we selected discordant variants on the MTOR gene between the affected and unaffected twin and we observed a mutation (rs2295079), placed in a region restricted to proximal 5′-UTR, as a strong possible causal variant. In addition, in most brain tissues (including fetal brain) evaluated for expression quantitative trait loci (eQTL), this locus is strongly correlated with post-translational modifications of histones (promoter and enhancer marks) and hypersensitivity to DNAse I (open chromatin mark). Taken together, our data suggest that changes in the MTOR gene may be related to CZS. Additional functional studies should be carried out to prove how and why a MTOR mutation can predispose the fetus to the syndrome. Abstract : Zika Virus; mTOR; Whole-exome sequencing; Twins; polymorphisms